2020
DOI: 10.3390/cancers12020332
|View full text |Cite
|
Sign up to set email alerts
|

Regorafenib Alteration of the BCL-xL/MCL-1 Ratio Provides a Therapeutic Opportunity for BH3-Mimetics in Hepatocellular Carcinoma Models

Abstract: Background: The multikinase inhibitor regorafenib, approved as second-line treatment for hepatocellular carcinoma (HCC) after sorafenib failure, may induce mitochondrial damage. BH3-mimetics, inhibitors of specific BCL-2 proteins, are valuable drugs in cancer therapy to amplify mitochondrial-dependent cell death. Methods: In in vitro and in vivo HCC models, we tested regorafenib’s effect on the BCL-2 network and the efficacy of BH3-mimetics on HCC treatment. Results: In hepatoma cell lines and Hep3B liver sphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“… Chemotherapy—standard chemotherapeutic agents such as doxorubicin and cisplatin are well-known inducers of mitochondrial ROS during their anti-tumoral action [ 159 , 160 ]. However, the mitochondrial effects of other more recently approved anti-cancer drugs, such as sorafenib or regorafenib, are being just revealed [ 161 , 162 ]. More importantly, mitochondrial antioxidants may reduce the effectivity of these drugs, while glutathione depressors potentiate their effect in hepatocellular carcinoma cells (Cucarull et al, unpublished results).…”
Section: Mgsh In Pathological Settingsmentioning
confidence: 99%
“… Chemotherapy—standard chemotherapeutic agents such as doxorubicin and cisplatin are well-known inducers of mitochondrial ROS during their anti-tumoral action [ 159 , 160 ]. However, the mitochondrial effects of other more recently approved anti-cancer drugs, such as sorafenib or regorafenib, are being just revealed [ 161 , 162 ]. More importantly, mitochondrial antioxidants may reduce the effectivity of these drugs, while glutathione depressors potentiate their effect in hepatocellular carcinoma cells (Cucarull et al, unpublished results).…”
Section: Mgsh In Pathological Settingsmentioning
confidence: 99%
“…Regorafenib was approved for treatment of unresectable HCC following progression on sorafenib in 2017 8 . In the past 3 years, lots of studies have focused on the antiproliferation and antiapoptosis of regorafenib in HCC cells, and its mechanisms involve in the inhibition of ERK/nuclear factor kappa B activation, Bcl‐xL/Mcl‐1 ratio, and Cyclin E1/Mcl‐1 signaling pathway, and so forth 30–32 . Importantly, regorafenib was approved for refractory mCRC in 2013, and a number of recent clinical trials for regorafenib were carried out in metastatic malignancies 11–13 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we observed a distinct reduction of tumor VM in the regorafenib-treated xenografts noted by CD34 − PAS + ( Figure 7D Mcl-1 signaling pathway, and so forth. [30][31][32] Importantly, regorafenib was approved for refractory mCRC in 2013, and a number of recent clinical trials for regorafenib were carried out in metastatic malignancies. [11][12][13] Nonetheless, the role of regorafenib in HCC metastasis and related mechanisms are still unclear.…”
Section: Regorafenib Suppresses Tumor Growth and Vm Formation In Pdmentioning
confidence: 99%
“…This study further elucidated that CKS1B plays a regulatory role in HCC through the JAK/STAT3 pathway and regulates the expression of STAT3 target genes, including Mcl-1, c-Myc, TIMP-1, Bcl-2 and VEGF. Among them, Mcl-1 and Bcl-2 exerted anti-apoptotic effects in HCC cells (Cucarull et al 2020 ), c-Myc and VEGF showed strong pro-tumor growth effects(Zhang et al 2020 ), and TIMP-1 was involved in the regulation of HCC metastasis (Wu et al 2020 ). Taken together, CKS1B was involved in HCC progression by influencing the expression of downstream target genes of JAK/STAT3 pathway.…”
Section: Discussionmentioning
confidence: 99%